Kajian Hermeneutik Terhadap Teks Sastra Indonesia Modern Dalam Perspektif Pembelajaran Bahasa Indonesia - Muhammad Afif; Ahmad Rizqi Pratama; Fitrah Arnanda Arfianto Putra; Muhammad Hasbullah Ridwan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The hermeneutic approach plays an important role in the analysis of literary texts by providing in-depth insight into the interpretation of meaning, cultural context and social dynamics contained in literary works. This research aims to identify and analyze the meaning contained in modern Indonesian literary texts through a hermeneutic approach, as well as exploring the application of the results of this analysis in Madrasah Aliyah Al Amiriyyah Indonesian language learning. The research method used is qualitative with a hermeneutic approach. Data was collected through analysis of modern Indonesian literary texts selected purposively. The analysis process involves stages of text interpretation, identification of main themes, and interpretation of meaning in cultural and social contexts. Research findings show that modern Indonesian literary texts contain various complex themes that reflect Indonesian social, cultural and political realities. In conclusion, hermeneutic studies of modern Indonesian literary texts help students understand the meaning of texts more deeply, as well as improve their critical and reflective skills in analyzing literary works.